Memory, identity and territory. Peasant colonization and peace construction: The self-management of memory in alto ariari (meta, Colombia) through its peasant organizations - Estrada Rodríguez, Johanne Alexis (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
This paper is the product of an ongoing doctoral research entitled: “Between Memory and History: Processes of peasant colonization of Alto Ariari, Meta-Colombia” and constitutes a theoretical and methodological approach to the relationship that interconnects the concepts of memory, identity, territory and peasant organization. This, through a colonization process that emerged after the second half of the 20th century in El Alto Ariari, a subregion of the department of Meta in the Colombian Orinoquía Region. The research evidences how the organizational experience of the peasantry and its struggle is still strong in the self-management of memory and territorial processes inherited to new generations for the sake of good living in the territory.